2012
DOI: 10.4067/s0718-34292012000100015
|View full text |Cite
|
Sign up to set email alerts
|

The serine protease inhibitors and plant-insect interaction

Abstract: Plants respond to a physical injury or biological attack by producing, among other compounds, an arsenal of defense proteins, secondary metabolites and phytohormones, all necessary for plant survival. Defense proteins include the group of serine protease inhibitors (SPI), proteins that interact with the active site of their target enzymes. The activity of these protease inhibitors has been exploited to combat insect pests. SPI is an interesting alternative to produce plants with improved resistance characters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Taken together, these results concluded that protease inhibitors extracted from B-serum latex were characterized as serine and/or cysteine-type protease inhibitors. In accordance with the literature, serine and cysteine protease inhibitors are two types found in large quantities in the cells (Habib & Fazili, 2007;Mendoza-Blanco & Casaretto, 2012;Popovic et al, 2013). Both of these PI are part of cell homeostasis playing a role in plant defense against pathogens (Hartl et al, 2011, Kim et al, 2009.…”
Section: Gambar 3 Profil Dari 26 Fraksi Protein Hasil Ion Exchange Cmentioning
confidence: 54%
“…Taken together, these results concluded that protease inhibitors extracted from B-serum latex were characterized as serine and/or cysteine-type protease inhibitors. In accordance with the literature, serine and cysteine protease inhibitors are two types found in large quantities in the cells (Habib & Fazili, 2007;Mendoza-Blanco & Casaretto, 2012;Popovic et al, 2013). Both of these PI are part of cell homeostasis playing a role in plant defense against pathogens (Hartl et al, 2011, Kim et al, 2009.…”
Section: Gambar 3 Profil Dari 26 Fraksi Protein Hasil Ion Exchange Cmentioning
confidence: 54%
“…Genes encoding Kunitz type inhibitors from legumes has been used to transform transgenic crop varieties in order to develop resistance to insects [62]. There are many studies that seek the relationship between the inhibitors of serine proteases present in plants and the coevolution with microorganisms, insects, nematodes, birds and mammals that may be related to the defense mechanisms of plants and the ability of these organisms to adapt to these mechanisms [63, 64].…”
Section: Resultsmentioning
confidence: 99%